2019
DOI: 10.4103/ijmr.ijmr_530_18
|View full text |Cite
|
Sign up to set email alerts
|

Histotyping of Indian thymomas: A clinicopathologic study from north India

Abstract: Background & objectives:Thymomas are rare, but most common anterior mediastinal lesions. The histomorphologic spectrum of thymic epithelial tumours (TETs) in Indian population has not been explored in depth. This study was aimed to assess the histomorphology of TETs in the Indian patients and correlate clinical parameters with pathological features.Methods:It was a retrospective study conducted in a tertiary referral hospital in north India. All morphologically confirmed cases of TETs since 2009 were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Contrary to the worldwide database, a large retrospective study on histotyping of Indian thymomas revealed B2 as the commonest histology. 28 In the present study, B2 was the commonest subtype, followed by B3, consistent with findings from another Indian study. 22 Together, B2 and B3 subtypes constituted more than 80% of our patient population.…”
Section: Discussionsupporting
confidence: 93%
“…Contrary to the worldwide database, a large retrospective study on histotyping of Indian thymomas revealed B2 as the commonest histology. 28 In the present study, B2 was the commonest subtype, followed by B3, consistent with findings from another Indian study. 22 Together, B2 and B3 subtypes constituted more than 80% of our patient population.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it will be interesting to see, whether multiomics analyses can still identify molecular thymoma features that segregate with racial-ethnic and environmental differences. Fourth, since the GTF2I mutation is largely restricted to type A and AB thymomas, the two patients cohorts were equally and strongly skewed towards an over-representation of these two histologies and are thus not representative regarding the histotype distribution ( 22 ). Therefore, future comparative studies between racially and ethnically disparate groups should comprise type B thymomas and thymic carcinomas as well.…”
Section: Discussionmentioning
confidence: 99%